2013
DOI: 10.1017/s1368980013001638
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an FFQ to assess antioxidant intake in overweight postmenopausal women

Abstract: Objective: To validate an FFQ to assess antioxidant intake in overweight postmenopausal women. Design: A seventy-four-item antioxidant 1-month FFQ was developed based on major antioxidant sources in the American diet. Forty overweight postmenopausal women participated in a 9-month observational study and completed four sets of FFQ and 7 d food record (7dFR) every 3 months. Twelve-hour fasting blood was collected for plasma antioxidant measurement at the first visit. Setting: Connecticut, USA. Subjects: Forty o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(64 reference statements)
0
3
1
Order By: Relevance
“…However, this second study only had 40 participants which may not be sufficient to accurately calculate the LOA [20]. Interestingly, despite the clinically wide LOA in the present study and literature, all had adequate agreement on a population level [36,37]. This indicates that the wide LOA obtained in the current study are not abnormal, therefore changes to the FFQ are not required at this stage.…”
Section: Agreement Between the Ffq And Reference Methodscontrasting
confidence: 49%
See 1 more Smart Citation
“…However, this second study only had 40 participants which may not be sufficient to accurately calculate the LOA [20]. Interestingly, despite the clinically wide LOA in the present study and literature, all had adequate agreement on a population level [36,37]. This indicates that the wide LOA obtained in the current study are not abnormal, therefore changes to the FFQ are not required at this stage.…”
Section: Agreement Between the Ffq And Reference Methodscontrasting
confidence: 49%
“…Previous studies have also observed wide LOA for vitamin C. In a study of 238 participants, the LOA ranged from −121.81 to 178.89 mg, with a bias of 28.54 mg [36]. Another study reported LOA of −110 to 120 mg, with a bias of 5 mg [37]. However, this second study only had 40 participants which may not be sufficient to accurately calculate the LOA [20].…”
Section: Agreement Between the Ffq And Reference Methodsmentioning
confidence: 73%
“…Published data suggest that mean α-tocopherol intakes in adults in some European countries (Finland, Sweden) (Amcoff et al, 2012;Helldán et al, 2013) are higher than those observed in the USA, where γ-tocopherol intakes are generally reported to be higher than in the EU (Gao et al, 2004;Maras et al, 2004;Dixon et al, 2006;Mahabir et al, 2008;Signorello et al, 2010;Yang et al, 2014a;Yang et al, 2014b).…”
Section: Dietary Intakementioning
confidence: 99%
“…The TAC values from diet and diet and supplements were highly correlated between the FFQ and 30‐day food records, whereas neither TAC from diet, nor TAC from diet and supplements was correlated with plasma TAC level. The feasibility in assessing long‐term antioxidant intake of the FFQ was later evaluated in 40 overweight postmenopausal women who participated in a 9‐month observational study and completed four sets of FFQ and 7‐day food record every 3 months . No significant seasonal variation of antioxidant intakes supports the applicability of this 1‐month FFQ with respect to capturing a usual dietary antioxidant pattern for these overweight postmenopausal women.…”
Section: The Development Of Tac Databases Of Foodsmentioning
confidence: 99%